Nusantarun Event Management Chapter 6 Wonosobo – Gunung Kidul 169 Km In 2018 (Journal of Physical Education and Sports, 2020)
Increasing the achievement of goals both in quality and quantity requires a management. Application to operating a donation event through good marathon running can be carried out well if there is good cooperation and coordination parties. The purpose of this research is to analysing the management design systems, program activities, funds, facilities and infrastructure. Analyzing the management design systems, program acitivities, funds, facilities and infrastructure. Analyze the movement system or management implementation, program activities, funds, facilities and infrastructure. Analyze the management supervision system, program activities, funds, facilities, and infrastructure. Analyze the evaluation system of management, program activities, funds, facilities, and infrastructure. Analyzing the impact NusantaRun Chapter 6 Wonosobo – Gunung Kidul 169 Km event in 2018. This research uses descriptive qualitative methods. The subjects in this study were the founder of NusantaRun, the running participants, and the surrounding community. This results of this study : The management design system, program activities, funds, facilities and infrastructure are well structured. Management organizing system, program activities, funds, facilities and infrastructure is clear and well organized. The system of movement or management, program activities, funds, facilities and infrastructure has been carried out properly in accordance with the objectives to be achieved. Management supervision system, program activities, funds, facilities and infrastructure have been implemented quite well. The impact of the NusantaRun Chapter 6 event is exemplary, because it can gives a social contribute to the community around Wonosobo – Gunung Kidul.